First stages of cultivation from chondracanthus chamissoi carpospores from three locations on the peruvian coast [Primeros estadios de cultivo a partir de carpósporas de chondracanthus chamissoi de tres localidades de la costa peruana] - Arbaiza S. (2019)
Chondracanthus chamissoi is a red seaweed of commercial importance that is intensively harvested along the Peruvian coast, so it is necessary to have a greater knowledge that leads to develop their cultivation. In this study, specimens from three locations were grown: Paiján (7°46’S; 79°25’W), Ancón (11°46’S; 77°11’W) and Mendieta (14°3’S; 76°15’W). The feasibility of the carpospores methodology is postulated as an alternative to develop its cultivation. In addition, it is proposed that there are similarities in reproductive potential (PR) and the first stages of culture (spore release, settlement and growth) between localities. The RP was higher for Ancón specimens (320 million of spores), followed by Mendieta (144 million) and Paiján (12 million). However, the spore release process for the start of the culture was more effective for Paiján, with an amount of carpospores released of 6.2 ± 1% of their PR (795,125 ± 141,121 carpospores per solution), followed by Mendieta with 0.8 ± 0.12% of its PR (1,134,500 ± 181,259) and Ancón with 0.4 ± 0.1% of their PR (1,342,625 ± 387,436). After 120 days of cultivation, a density of 31 seedlings per cm2 was obtained for Ancón, 49 for Mendieta and 18 for Paiján. It is concluded that the culture of C. chamissoi using the carpospore methodology is possible. Likewise, there are differences between the PR values and first stages of cultivation of C. chamissoi from three different locations.